Jump to content

limit of ((x(sqrt(x+2)))/sqrt(x+1))-x is 1/2? Why?


Recommended Posts

I need this limit ((x(sqrt(x+2)))/sqrt(x+1))-x to calculate the asymptote of this function: ((x(sqrt(x+2)))/sqrt(x+1)).

which, according to the class notes: y=x+1/2

with a = 1, b = 1/2

However, the online math calculators say that currently no steps are supported to show for this kind of problem.


I calculated this limit as x*sqrt(1)-x = 1, but apparently the correct answer is 1/2.


What is my mistake?


Thx in advance.


r

post-119234-0-27878800-1469737028_thumb.png

Link to post
Share on other sites
  • 1 month later...

You should use l'Hôpital's rule for a rigorous proof:
[math]\lim_{x\to\infty} {\frac{x\sqrt{x+2}}{\sqrt{x+1}}-x}=\lim_{x\to\infty} {\frac{x}{\sqrt{(x+1)(x+2)}+x+1}}[/math] (see the previous post).

Using l'Hôpital's rule, this equals [math]\lim_{x\to\infty} {\frac{1}{(\sqrt{(x+1)(x+2)})'+1}}=\lim_{x\to\infty} {\frac{1}{\frac{2x+3}{2\sqrt{(x+1)(x+2)}}+1}}[/math]. Assuming the limit exists, this is equal to [math]\frac{1}{\lim_{x\to\infty} {\frac{2x+3}{2\sqrt{(x+1)(x+2)}}}+1}[/math].

You then evaluate [math]\lim_{x\to\infty} {\frac{2x+3}{2\sqrt{(x+1)(x+2)}}}[/math]: Using l'Hôpital again, this is equal to [math]\lim_{x\to\infty} {\frac{2}{\frac{2(2x+3)}{2\sqrt{(x+1)(x+2)}}}}=\lim_{x\to\infty} {\frac{2\sqrt{(x+1)(x+2)}}{2x+3}}[/math]. It follows that this limit is 1, and therefore [math]\lim_{x\to\infty} {\frac{x\sqrt{x+2}}{\sqrt{x+1}}-x}=\frac{1}{1+1}=\frac{1}{2}[/math].

Edited by renerpho
Link to post
Share on other sites
  • 3 months later...

Create an account or sign in to comment

You need to be a member in order to leave a comment

Create an account

Sign up for a new account in our community. It's easy!

Register a new account

Sign in

Already have an account? Sign in here.

Sign In Now
×
×
  • Create New...

Important Information

We have placed cookies on your device to help make this website better. You can adjust your cookie settings, otherwise we'll assume you're okay to continue.